2021
DOI: 10.1007/s11664-021-09348-y
|View full text |Cite
|
Sign up to set email alerts
|

Weak Ferromagnetism in the FeCr2O4 Semiconductor Spinel with Half-Metallic Feature in the Ground State

Abstract: Materials with multifunctional properties are currently being studied for countless technological applications. In the present work, an experimental and theoretical study of the iron-chromite spinel FeCr 2 O 4 produced by the solid-state reaction technique is reported. Structural analysis from x-ray diffraction experiments revealed the crystallization of the material into a cubic structure and morphological and compositional studies showed the granular character, with nanometric and micrometric dimensions whos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Based on the electronic properties we have also observed that most of the material exfoliated are semiconductors, such as α‐WO 3 , [ 64,119 ] LiMn 2 O 4 , [ 65,120 ] β‐B, [ 121,122 ] α‐Fe 2 O 3 , [ 68,123 ] FeCr 2 O 4 , [ 70,124 ] FeTiO 3 , [ 69,125 ] MnTe, [ 71 ] PbS, [ 75,126 ] α‐FeO(OH), [ 127 ] SiC, [ 76 ] B 4 C, [ 128 ] FeS 2 , [ 79,123 ] Ge, [ 129 ] Si, [ 129 ] TiC, [ 130 ] and WC. [ 131 ] This is very important because all these materials are fundamentally different, as semiconductors such as silicon, germanium, etc.…”
Section: Lpe Of Nonlayered Non‐van‐der‐waals (Nl‐nvdw) Compoundsmentioning
confidence: 99%
“…Based on the electronic properties we have also observed that most of the material exfoliated are semiconductors, such as α‐WO 3 , [ 64,119 ] LiMn 2 O 4 , [ 65,120 ] β‐B, [ 121,122 ] α‐Fe 2 O 3 , [ 68,123 ] FeCr 2 O 4 , [ 70,124 ] FeTiO 3 , [ 69,125 ] MnTe, [ 71 ] PbS, [ 75,126 ] α‐FeO(OH), [ 127 ] SiC, [ 76 ] B 4 C, [ 128 ] FeS 2 , [ 79,123 ] Ge, [ 129 ] Si, [ 129 ] TiC, [ 130 ] and WC. [ 131 ] This is very important because all these materials are fundamentally different, as semiconductors such as silicon, germanium, etc.…”
Section: Lpe Of Nonlayered Non‐van‐der‐waals (Nl‐nvdw) Compoundsmentioning
confidence: 99%
“…in magnetic systems, which opens up many possibilities in magnetism-mediated TE materials. In future research, not only half metallic systems such as spinel ferrites (FeCr 2 O 4 and VFe 2 O 4 ), [66][67][68] but nonmagnetic semiconductors doped with magnetic impurities, such as Cr x Sb 2−x Te 3 , 69 Fe x Bi 2−x Te 3 70 and Fe x (Bi, Sb) 2−x Te 3 71 which possess weak ferromagnetism and a low carrier concentration, could be promising systems to implement the proposed strategy.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the spin polarization relaxation via the introduction of antiferromagnetic coupling between host magnetic ions and magnetic impurities can be utilized as a general strategy to enhance the Seebeck coefficient in magnetic systems, which opens up many possibilities in magnetism-mediated TE materials. In future research, not only half metallic systems such as spinel ferrites (FeCr 2 O 4 and VFe 2 O 4 ), 66–68 but nonmagnetic semiconductors doped with magnetic impurities, such as Cr x Sb 2− x Te 3 , 69 Fe x Bi 2− x Te 3 70 and Fe x (Bi, Sb) 2− x Te 3 71 which possess weak ferromagnetism and a low carrier concentration, could be promising systems to implement the proposed strategy.…”
Section: Discussionmentioning
confidence: 99%